German Legal Translation in MGIMO: European Union Law - R. O. Raynkhardt (Научный диалог)
The author presents a review on the textbook on legal translation “German Language. European Union Law (General Part)” prepared by specialists of MGIMO-University and published in 2017. It is noted that this publication can be used not only as a textbook on translation, but also as a guidebook for the legal system of the European Union.